FREQUENCY OF CALR GENE MUTATION IN MYELOPROLIFERATIVE NEOPLASMS - Latif, Sana; Khan, Saleem Ahmed; Mahmood, Asad; Robert, Helen Mary; Mahmood, Rafia (Pakistan Armed Forces Medical Journal, 2020)
Objective: To detect the calreticulin gene mutation in myeloproliferative neoplasms and its clinicohaematological correlation.Study Design: Cross sectional study.Place and Duration of Study: Armed Forces Institute of Pathology, from Jun 2017 to Jun 2018.Methodology: A cross sectional study was conducted at Department of Haematology, Armed Forces Institute of Pathology from June 2017 to June 2018. A total of 48 newly diagnosed JAK2V617F patients with negative myeloproliferative neoplasma were enrolled in the study. Clinico-haematologic features were noted. DNA was extracted from bone marrow samples. Molecular analysis was performed for Calreticulin gene by Sanger Sequencing. Results were analysed by using Genetic Analyser HITACHI 3130.Results: Of 48 newly diagnosed JAK2V617F negative myeloproliferative neoplasms patients, 38 were male and 10 were females with M:F ratio of 3.8:1. Mean age was 43.5 years (standard deviation ± 15). 9 (18.8%) were diagnosed as polycythemia vera, 21 (43.8%) as Essential thrombocythemia and 18 (37.5%) as having Primary myelofibrosis. CALR mutation was detected in four (8%) of myeloproliferative neoplasms cases. Out of four CALR positive cases, three were diagnosed to have Primary myelofibrosis while only one had a diagnosis of Essential thrombocythemia. Conclusion: We conclude that CALR mutation was an important molecular marker in JAK2V617F negative patients. Primary myelofibrosis shares a high rate of CALR mutation as compared to polycythemia vera and essential thrombocythemia.